Experiencing the impossible : the science of magic - Kuhn, Gustav (Cambridge [etc.] MIT Press, 2019)
"Magic is one of the most enduring forms of entertainment and poses some of the most fundamental philosophical and psychological questions. Despite this, perhaps surprisingly, magic has received very little attention from people outside its sphere. In recent years psychologists, neuroscientists and philosophers have started to study magic more systematically, and the science of magic is now a field of its own. We now have scientific data that helps explain psychological and neurological mechanisms that underpin these mystifying experiences. The author is a magician and psychologist, and in this book, he discusses the latest scientific research on magic, which provides intriguing, and often unsettling insights into the mysteries of the human mind. Magic exploits surprising, and often counterintuitive psychological principles, and understanding these cognitive processes will challenge your beliefs about your own capabilities. How much of your world do you really perceive? Can you trust what you see and remember? Who is in charge of your thoughts and actions? In the final part we will see how magic is applied to areas outside entertainment and discuss some of the reasons we so captivated by this art from. Experiencing the Impossible will help you appreciate the complex, and almost magical neurological mechanisms that underpin many of our daily activities"-- Provided by publisher
Keywords: Magia